Eco-Friendly Synthesis of ZnO/CQD Photocatalysts from Waste Milk for Myclobutanil Degradation under Visible Light - Orien Prilita; Hanaiyah Parasdila; Risa Suryana; Osi Arutanti; Hendri Widiyandari (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
Pesticides play a vital role in maintaining the global food supply amid rising agricultural demand and the adverse effects of climate change on crop productivity. Among them, myclobutanil, a triazole-based compound, is commonly used to safeguard plants against fungal diseases. The chemical compounds produced from the high toxicity, mobility, and persistence of pesticides in water can have harmful environmental effects. Food/organic waste has recently gained attention for its potential use in material research, one of them is stale milk. Stale milk contains lactic acid, which can be utilized as a carbon precursor for preparing carbon quantum dot (CQD). In this study, a ZnO/CQD composite photocatalyst was successfully synthesized using CQD derived from stale milk through a green hydrothermal method. The photocatalytic activity of ZnO/CQD in degrading the pesticide myclobutanil was confirmed after 120 min, achieving a degradation efficiency of 30% while ZnO only 18% under visible light, demonstrating its potential as an excellent photocatalyst candidate for the removal of organic pollutants. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).